Impact of the Medicare Shared Savings Program on utilization of mental health and substance use services by eligibility and race/ethnicity. (5th February 2021) - Acevedo, Andrea; Mullin, Brian O.; Progovac, Ana M.; Caputi, Theodore L.; McWilliams, J. Michael; Cook, Benjamin L.
Abstract: Objective: To assess the impact of the Medicare Shared Savings Program (MSSP) ACOs on mental health and substance use services utilization and racial/ethnic disparities in care for these conditions. Data sources: Five percent random sample of Medicare claims from 2009 to 2016. Study design: We compared Medicare beneficiaries in MSSP ACOs to non‐MSSP beneficiaries, stratifying analyses by Medicare eligibility (disability vs age 65+). We estimated difference‐in‐difference models of MSSP ACOs on mental health and substance use visits (outpatient and inpatient), medication fills, and adequate care for depression adjusting for age, sex, race/ethnicity, region, and chronic medical and behavioral health conditions. To examine the differential impact of MSSP on our outcomes by race/ethnicity, we used a difference‐in‐difference‐in‐differences (DDD) design. Data collection/extraction methods: Not applicable. Principal findings: MSSP ACOs were associated with small reductions in outpatient mental health (Coeff: −0.012, P  < .001) and substance use (Coeff: −0.001, P  < .01) visits in the disability population, and in adequate care for depression for both the disability‐ and age‐eligible populations (Coeff: −0.028, P  < .001; Coeff: −0.012, P  < .001, respectively). MSSP ACO's were also associated with increases in psychotropic medications (Coeff: 0.007 and Coeff: 0.0213, for disability‐ and age‐eligible populations, respectively, both P  < .001) and reductions in inpatient mental health stays (Coeff:‐0.004, P  < .001, and Coeff:‐0.0002, P  < .01 for disability‐ and age‐eligible populations, respectively) and substance use‐related stays for disability‐eligible populations (Coeff:‐0.0005, P <.05). The MSSP effect on disparities varied depending on type of service. Conclusions: We found small reductions in outpatient and inpatient stays and in rates of adequate care for depression associated with MSSP ACOs. As MSSP ACOs are placed at more financial risk for population‐based treatment, it will be important to include more robust behavioral health quality measures in their contracts and to monitor disparities in care.